LPD digitalization in the mobile banking era: How customer perception affects M-Pise adoption? - Pradnyasari, Putu Dian; Ekawati, Ni Wayan (International research journal of management, IT and social sciences, 2025)
For microfinance organizations like LPD (Lembaga Perkreditan Desa), mobile banking improves both transaction efficiency and financial inclusion. This technology has been implemented in LPD Desa Adat Kesiman through M-Pise, although the rate of acceptance is still low. The purpose of this research is to examine the elements that impact the interest in using M-Pise at LPD Desa Adat Kesiman using the Technology Acceptance Model (TAM). The link between trust, simplicity of use, and perceived usefulness is moderated by attitude toward utilizing. Through a survey, 200 clients who were not yet M-Pise users provided data that was evaluated using SEM-PLS. Attitude toward using mediates the connection between attitude toward using and desire to use, with intention to use serving as a partial mediator and all three components having positive and substantial impacts on these outcomes. Finally, consumers' positive opinions of M-Pise are increased by the perceived benefits, convenience of use, and trust, increasing their propensity to embrace the service. To encourage mobile banking within its community, LPD should prioritize improving digital literacy, enhancing service features, and bolstering application security, according to the practical implications.